2016
DOI: 10.1002/adsc.201600670
|View full text |Cite
|
Sign up to set email alerts
|

Stereocontrolled [4+1] Annulation of α‐Hydroxycyclobutenones: Synthesis of Polysubstituted Cyclopentenones

Abstract: As tereocontrolled [4+ +1] annulation of ahydroxycyclobutenonesh as been disclosed. Fort he first time, a-hydroxycyclobutenones have been proven as facile diene precursors for [4+ +1] annulation. Meanwhile,t he reported transformation presents ac oncise synthetic route to polysubstituted cyclopentenones with high stereoselectivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…A number of cycloaddition reactions of cyclobutenones have been reported, and most of them have been summarized in the review published in 2016 . New entries include cycloaddition reactions of cyclobutenone 320 with imine 321 and diazomethane 323 , and a cycloaddition reaction of benzocyclobutenone 254 with isatin 325 (Scheme ). …”
Section: Cyclobutanonesmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of cycloaddition reactions of cyclobutenones have been reported, and most of them have been summarized in the review published in 2016 . New entries include cycloaddition reactions of cyclobutenone 320 with imine 321 and diazomethane 323 , and a cycloaddition reaction of benzocyclobutenone 254 with isatin 325 (Scheme ). …”
Section: Cyclobutanonesmentioning
confidence: 99%
“…They are kinetically inert and thermodynamically stable, and thus, difficult to cleave. 1 When they are structurally strained, however, their cleavage becomes significantly more feasible. Release of the structural strain offers a dynamic momentum as well as a thermodynamic driving force for their transformations.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Hu and co-workers reported the stereoselective transformation of 4-hydroxycyclobutenones into polysubstituted 5-(trimethylsilyl)cyclopentenones by formal [4 + 1] annulation with trimethylsilyldiazomethane (TM-SCHN 2 ). 13 Because cyclopentenones are useful building blocks for the synthesis of bioactive molecules, 14 T. Kurohara et al…”
Section: Scheme 4 Three-step Telescoping Synthesis Of Quinones 6a-f mentioning
confidence: 99%
“…The observed relative configurations of 11f were in good agreement with the mechanism originally proposed by Hu and co-workers. 13 We previously demonstrated that the CF 3 -semisquarate can be efficiently functionalized by electrophilic addition of unsaturated organosilanes. 5b Thus, the compatibility of the EtO 2 CCF 2 group with Lewis acid promoted Hosomi-Sakurai-type allylation and Mukaiyama-type aldol reaction conditions was investigated (Scheme 7).…”
Section: Paper Syn Thesismentioning
confidence: 99%
See 1 more Smart Citation